A New Approach for β-cyclodextrin Conjugated Drug Delivery System in Cancer Therapy - Sheng, Teng M.; Kumar, Palanirajan Vijayaraj (Current Drug Delivery, 2022)
Natural cyclodextrins (CDs) are macrocyclic starch molecules discovered a decade ago, in which α-, β-, and γ-CD were commonly used. They originally acted as pharmaceutical excipients to enhance the aqueous solubility and alter the physicochemical properties of drugs that fall under class II and IV categories according to the Biopharmaceutics Classification System (BPS). The industrial significance of CDs became apparent during the 1970s as scientists started to discover more of CD’s potential in chemical modifications and the formation of inclusion complexes. CDs can help in masking and prolonging the half-life of drugs used in cancer. Multiple optimization techniques were discovered to prepare the derivatives of CDs and increase their complexation and drug delivery efficiency. In recent years, due to the advancement of nanotechnology in pharmaceutical sectors, there has been growing interest in CDs. This review mainly focuses on the formulation of cyclodextrin conjugated nanocarriers using graphenes, carbon nanotubes, nanosponges, hydrogels, dendrimers, and polymers to achieve drug-release characteristics specific to cells. These approaches benefit the discovery of novel anti-cancer treatments, solubilization of new drug compounds, and cell specific drug delivery properties. Due to these unique properties of CDs, they are essential in achieving and enhancing tumor-specific cancer treatment.
Keywords: Cyclodextrin